La ruptura de tabúes en la literatura hebrea. Pinjás Sadé: entre transgresión y revelación - Varela Moreno, Mª Encarnación (’Ilu. Revista de Ciencias de las Religiones, 2009)
Pinhas Sadeh was considered as an unorthodox writer as regards his environment, the “State Culture” in Israel. In the first part of this paper I present the biography of the author and his most representative work, Life as a parable, published in 1958, as well as his romantic and frankist roots and his leaning towards Christianity according to the Gospel. In the second part a mythical analysis of this work is made according to the inner journey of hero, through which the main character is looking for his life meaning. In this second part I present my methodology, based on works of the Eranos Society (Mircea Eliade, C.G. Jung, Gilbert Durand). Afterwards, I analyse the mithems that I have found in Life as a parable. Finally, I make a mythical comparison between this novel and Siddharta, of Hermann Hesse.